Motion Graphic Sebagai Media Promosi SMK Telkom 1 Medan Sumatera Utara - Erdhina Adi, Anggar; Anwar, Ardy Aprilian; Tri Lestari, Martha; Djuwita, Amalia; Windya Giri, Refi Rifaldi; Millanyani, Heppy (Besaung : Jurnal Seni Desain dan Budaya, 2024)
The development of information and communication technology (ICT) has brought significant changes in various aspects of life, including in the world of education. Telkom 1 Medan Vocational School, as one of the leading vocational schools in the city of Medan, needs to formulate appropriate promotional strategies to attract the interest of prospective students in the digital era. This research aims to identify appropriate social media content visualizations to attract prospective students at Telkom 1 Medan Vocational School, especially in the city of Medan. This research uses qualitative research methods with a descriptive approach. Data was collected through observation of Telkom Medan Vocational School's social media, in-depth interviews with prospective students, visual analysis of social media content at other vocational schools, and focus group discussions with social media and education experts. The data analysis techniques used are content analysis and thematic analysis. The research results show that the right visualization of social media content to attract prospective Telkom Medan Vocational School students in the city of Medan must have several characteristics, namely Informative, Interesting, Interactive, Relevant and Building a positive image. Visualization of social media content made capable effective promotional strategy to attract prospective students at SMK Telkom 1 Medan in the digital era.